PRODUCTIVITY OF MILK AND MILK COMPOSITION OF AN INDIGENOUS SHEEP BREED IN MACEDONIA - N. Pacinovski2, V. Dzabirski3, K. Porcu3, E. Joshevska4, G. Cilev5, M. P. Petrovic6 (My University, 2015)
Abstract: Several production traits have been examined in 180 Ovchepolian sheep during a four-year production period (2010–2013). The sheep ranged in age from the first to the 7th lactation and 4319 individual lactation controls were realized in total. Besides the basic statistics, all data were analysed using a multi-factorial fixed model. The influence of certain factors was studied using the F-test and the analyses were made using the SPSS set of programs. Most of the factors (year, lactation, lambing month and number of milk recording) had a highly significant influence (P<0.001) on daily milk production (milk from the morning, evening and the total amount of milk, % of milk fat and kg fat) in this breed of sheep. The month of milk recording also had a significant influence (P<0.05) on all traits. Only fertility had no impact on the variations in the tested parameters, aside from the total daily milk, on which a highly significant influence was manifested (P<0.01). The average milk lactation among the tested sheep population during all four years was, on average, 58 ± 0.247 l, while the production of milked milk for the same period was 37 ± 0.217 l. The length of the lactation period in these sheep for the four years studied averaged 182 ± 0.31 days. The maximal daily milk yield in this sheep population was measured in 2011 (0.302 ± 0.26 l). Regarding their age, the highest daily milk yield was determined in sheep in the third lactation (0.365 ± 0.26), while those in the 7th lactation had the lowest (0.255 ± 0.27).
Keywords: Ovchepolian sheep, daily milk production; fat %; fat kg; influencing factors